Pengaruh Panic Buying dan Harga Terhadap Pembelian Produk Bear Brand Pada Masa Pandemi Covid-19 - Nesya Dea Derana; Iskandar Ali Alam (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The goal of this study is to examine the influence of panic purchasing prices on the purchase of Bear Brand items during the Covid-19 Pandemic Period. The demographic of this research is Bear Brand customers, using the Lemeshow formula it is known that the sample in the study is 50 persons. The technique of analysis employing Multiple Linear Regression analysis. The findings of the research revealed that panic purchasing and pricing combination had a substantial influence on the purchase of Bear Brand items. It is hoped that with this research Bear Brand can maintain the stability of panic buying and good prices for customers so that they can attract customers' interest in buying Bear Brand products.